EE Tech News Edition 2 2018/ Faculty of Electrical Engineering UiTM Terengganu - UiTM Terengganu, Faculty of Electrical Engineering (Faculty of Electrical Engineering, UiTM Terengganu, 2018)
Includes articles and activities held by Faculty of Electrical Engineering's students and staffs at UiTM Terengganu Dungun Campus.